2020
DOI: 10.1016/j.psj.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Growth and humoral immune effects of dietary Original XPC in layer pullets challenged with Mycoplasma gallisepticum

Abstract: Effects of dietary Original XPC (XPC) in commercial layer pullets challenged with the virulent, low passage R strain of Mycoplasma gallisepticum (R low MG) were investigated. Hy-Line W-36 pullets sourced from MG-clean breeders were fed a basal diet with or without (CON) XPC (1.25 kg/metric ton) from hatch until 12 wk of age (woa). At 8 and 10 woa, half of the birds in each dietary treatment were challenged with R low MG. Body weight was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…In the previous companion trial by Elliott et al. (2020) in which the same birds were tested, it was shown that all birds in the control and XPC dietary treatment groups tested negative for MG-specific serum IgM and IgG antibody titers before the first 8 woa challenge.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In the previous companion trial by Elliott et al. (2020) in which the same birds were tested, it was shown that all birds in the control and XPC dietary treatment groups tested negative for MG-specific serum IgM and IgG antibody titers before the first 8 woa challenge.…”
Section: Resultsmentioning
confidence: 96%
“…Beginning on the day of hatch, Hy-Line W-36 pullets were continuously fed 1 of 2 dietary treatments for the duration of the study (12 woa). The dietary treatments were a basal control diet ( CON ) or a basal control diet containing XPC at 1.25 kg/metric ton ( Elliott et al., 2020 ). In each of 4 rooms in an environmentally controlled facility, there were 2 replicate floor pens belonging to each of the 2 dietary treatments (4 pens per room; 16 total pens).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations